Treatments for hyperemesis gravidarum and nausea and vomiting in pregnancy: a systematic review and economic assessment - O’Donnell, Amy; McParlin, Catherine; Robson, Stephen C; Beyer, Fiona; Moloney, Eoin; Bryant, Andrew; Bradley, Jennifer; Muirhead, Colin; Nelson-Piercy, Catherine; Newbury-Birch, Dorothy; Norman, Justine; Simpson, Emma; et al. (Health technology assessment (Winchester, England), 2016)
Nausea and vomiting in pregnancy (NVP) affects up to 85% of all women during pregnancy, but for the majority self-management suffices. For the remainder, symptoms are more severe and the most severe form of NVP - hyperemesis gravidarum (HG) - affects 0.3-1.0% of pregnant women. There is no widely accepted point at which NVP becomes HG. This study aimed to determine the relative clinical effectiveness and cost-effectiveness of treatments for NVP and HG. MEDLINE, EMBASE, Cumulative Index to Nursing and Allied Health Literature, Cochrane Central Register of Controlled Trials, PsycINFO, Commonwealth Agricultural Bureaux (CAB) Abstracts, Latin American and Caribbean Health Sciences Literature, Allied and Complementary Medicine Database, British Nursing Index, Science Citation Index, Social Sciences Citation Index, Scopus, Conference Proceedings Index, NHS Economic Evaluation Database, Health Economic Evaluations Database, China National Knowledge Infrastructure, Cochrane Database of Systematic Reviews and Database of Abstracts of Reviews of Effects were searched from inception to September 2014. References from studies and literature reviews identified were also examined. was hand-searched, as were websites of relevant organisations. Costs came from NHS sources. A systematic review of randomised and non-randomised controlled trials (RCTs) for effectiveness, and population-based case series for adverse events and fetal outcomes. Treatments: vitamins B6 and B12, ginger, acupressure/acupuncture, hypnotherapy, antiemetics, dopamine antagonists, 5-hydroxytryptamine receptor antagonists, intravenous (i.v.) fluids, corticosteroids, enteral and parenteral feeding or other novel treatment. Two reviewers extracted data and quality assessed studies. Results were narratively synthesised; planned meta-analysis was not possible due to heterogeneity and incomplete reporting. A simple economic evaluation considered the implied values of treatments. Seventy-three studies (75 reports) met the inclusion criteria. For RCTs, 33 and 11 studies had a low and high risk of bias respectively. For the remainder ( = 20) it was unclear. The non-randomised studies ( = 9) were low quality. There were 33 separate comparators. The most common were acupressure versus placebo ( = 12); steroid versus usual treatment ( = 7); ginger versus placebo ( = 6); ginger versus vitamin B6 ( = 6); and vitamin B6 versus placebo ( = 4). There was evidence that ginger, antihistamines, metoclopramide (mild disease) and vitamin B6 (mild to severe disease) are better than placebo. Diclectin [Duchesnay Inc.; doxylamine succinate (10 mg) plus pyridoxine hydrochloride (10 mg) slow release tablet] is more effective than placebo and ondansetron is more effective at reducing nausea than pyridoxine plus doxylamine. Diclectin before symptoms of NVP begin for women at high risk of severe NVP recurrence reduces risk of moderate/severe NVP compared with taking Diclectin once symptoms begin. Promethazine is as, and ondansetron is more, effective than metoclopramide for severe NVP/HG. I.v. fluids help correct dehydration and improve symptoms. Dextrose saline may be more effective at reducing nausea than normal saline. Transdermal clonidine patches may be effective for severe HG. Enteral feeding is effective but extreme method treatment for very severe symptoms. Day case management for moderate/severe symptoms is feasible, acceptable and as effective as inpatient care. For all other interventions and comparisons, evidence is unclear. The economic analysis was limited by lack of effectiveness data, but comparison of costs between treatments highlights the implications of different choices. The main limitations were the quantity and quality of the data available. There was evidence of some improvement in symptoms for some treatments, but these data may not be transferable across disease severities. Methodologically sound and larger trials of the main therapies considered within the UK NHS are needed. This study is registered as PROSPERO CRD42013006642. The National Institute for Health Research Health Technology Assessment programme.